2023
DOI: 10.21203/rs.3.rs-2901655/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular mechanisms and prognostic value of the selenoprotein gene family in lung adenocarcinoma and lung squamous cell carcinoma

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide, and has the highest morbidity among all cancers. Non-small cell lung cancer (NSCLC) accounts for 85% of all lung cancer cases and its most common subtypes are lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC). Although the selenium protein gene plays a key role in the initiation, development, and progression of many cancers, the panoramic picture of the involvement of selenoprotein gene family in LUAD and LUSC is unclear. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Interestingly, we identified a marker, GPX1, which showed higher gene and protein expressions in ALK-rearranged pADCs compared to NATs, but not in ALK-negative pADCs. On the contrary, both studies by Wen et al [30] and Tian et al [31] identified GPX1 as being downregulated in lung tumors compared to NATs. A previous study suggests that GPX1 may induce cisplatin-based chemoresistance in NSCLC [32], but the exact role of this gene in lung cancer is still unclear [33].…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, we identified a marker, GPX1, which showed higher gene and protein expressions in ALK-rearranged pADCs compared to NATs, but not in ALK-negative pADCs. On the contrary, both studies by Wen et al [30] and Tian et al [31] identified GPX1 as being downregulated in lung tumors compared to NATs. A previous study suggests that GPX1 may induce cisplatin-based chemoresistance in NSCLC [32], but the exact role of this gene in lung cancer is still unclear [33].…”
Section: Discussionmentioning
confidence: 84%